A randomized controlled trial of attention bias modification training for socially anxious adolescents. (September 2016) - Fitzgerald, Amanda; Rawdon, Caroline; Dooley, Barbara
Abstract: The current study aimed to examine the efficacy of attention bias modification (ABM) training to reduce social anxiety in a community-based sample of adolescents 15–18 years. The study used a single-blind, parallel group, randomized controlled trial design (Clinical Trials ID:NCT02270671 ). Participants were screened in second-level schools using a social anxiety questionnaire. 130 participants scoring ≥24 on the Social Phobia and Anxiety Inventory for Children (SPAI-C) were randomized to the ABM training ( n = 66)/placebo ( n = 64) group, 120 of which completed pre-, post-, and 12-week follow-up data collection including threat bias, anxiety, and depression measures. The ABM intervention included 4 weekly training sessions using a dot-probe task designed to reduce attention bias to threatening stimuli. ABM training did not alter the primary outcomes of attention bias to threat or social anxiety symptoms raising questions about the efficacy of ABM as an intervention for adolescents. Highlights: Attention bias modification (ABM) training for social anxiety was tested. 120 adolescents with social anxiety were treated with ABM or placebo training. ABM training did not alter attention bias to threat or social anxiety. Questions about the efficacy of ABMT as an intervention are raised.